Utilization of Pyrolysed Tyres Scrap as Heavy Metal Adsorbent - Surya, Surya; Trihadiningrum, Yulinah; Nisaa, Ainul Firdatun (Universitas Diponegoro, 2025)
Scrap tires continuously generated due to increasing motorized vehicle use. In Indonesia, tire waste generation reaches approximately 11 million tons annually. One processing method is pyrolysis, which converts tires into carbon, oil, and metals. However, the carbon, comprising 25–30% of tire conten, remains underutilized. This study aims to compare the performance of Tire-derived Activated Carbon (TAC) and Commercial Activated Carbon (CAC) in Pb(II) removal from wastewater. The carbon was activated using 98% H₂SO₄ (1:1 w/w) and heated in a fluidized bed reactor at 600, 650, and 700 °C for 1 hour. The optimal TAC was produced at 600 °C, with a specific surface area of 103.162 m²/g. FTIR analysis confirmed the presence of -OH, C=C, and C=O functional groups, and SEM revealed a porous structure. Adsorption tests at varying pH and initial Pb(II) concentrations showed optimum performance at pH 5 and 30 mg/L. The Langmuir model fitted the data well, indicating monolayer adsorption on a homogeneous surface. TAC achieved 96.32% removal efficiency in synthetis medium and a maximum adsorption capacity of 240.80 mg/g, significantly higher than CAC (62.68%, 151.366 mg/g). These results demonstrate the potential of TAC as an effective low-cost alternative adsorbent for heavy metal removal.